PEMANFAATAN EKSTRAK TANAMAN ROSEMARRY TERHADAP KUALITAS SUSU KAMBING PASTEURISASI: UTILIZATION OF ROSEMARRY PLANT EXTRACT ON THE QUALITY OF PASTEURIZATION GOAT MILK - Pratama, Meylano Novi; Abdurrahman, Zakaria Husein; Purwadi, Purwadi (Universitas Boyolali, 2025)
This study aimed to determine the effect of rosemary addition on the quality of pasteurized goat milk. The materials used in the study were Peranakan Etawa goat milk, rosemary, water, and sugar. A Completely Randomized Design was used, consisting of four treatments and five replications. The treatments included: P0 = pasteurized milk without rosemary (control), P1 = pasteurized milk with 1.5 g of rosemary in 50 ml solution, P2 = pasteurized milk with 3 g of rosemary in 50 ml solution, and P3 = pasteurized milk with 4.5 g of rosemary in 50 ml solution. Data were analyzed using analysis of variance (ANOVA). The results showed that the addition of rosemary significantly affected the organoleptic quality and hedonic test outcomes, which were conducted at the University of Boyolali. Organoleptic testing revealed a highly significant effect (P<0.01) on taste, aroma, and color. The hedonic test also showed a significant effect (P<0.01) on panelists' preference for milk with rosemary addition. The Total Plate Count (TPC) test indicated that rosemary extract significantly (P<0.01) reduced the number of bacteria in pasteurized milk. In conclusion, rosemary addition influenced the organoleptic quality of pasteurized goat milk in terms of taste and aroma, although it had no effect on color. The hedonic test results indicated that rosemary-added milk was less preferred in terms of taste, aroma, and texture, although the aroma was still acceptable to panelists. Furthermore, increasing the concentration of rosemary resulted in a greater reduction in bacterial count in pasteurized milk.